Implementation of a Remote Instrumental Music Course Focused on Creativity, Interaction, and Bodily Movement. Preliminary Insights and Thematic Analysis - Schiavio, Andrea; Nijs, Luc (Frontiers in Psychology, 2022)
In a newly designed collaborative online music course, four musical novices unknown to each other learned to play the clarinet, starting from zero. Over the course of 12 lessons, a special emphasis was placed on mutual interaction, creativity, and bodily movement. Although addressing these dimensions might be particularly challenging in distance learning contexts, a thematic analysis of semi-structured interviews with the learners revealed how the teaching approach proposed has generally facilitated learning. Qualitative findings highlight the importance of establishing meaningful relationships with the musical instrument as well as with other students to build musicality, and of the interplay between creativity and control in individual and collective music-making activities. We suggest that remote music tuition with a small group can be a valuable resource to start learning music, and that a creative, collaborative, and movement-based approach can contribute to musical growth and skill acquisition.